Leaky Director Networks and Innovation Herding - Cabezon, Felipe; Hoberg, Gerard (Review of Financial Studies, 2026)
We first document that, despite potential legal issues, overlapping directors are surprisingly prevalent among direct competitors. Using panel data regressions and plausibly exogenous shocks, we find that competing firms in markets with dense overlapping-director networks experience innovation herding, lose product differentiation, and, ultimately, perform poorly. Novel text-based network propagation tests of technologies show that intellectual property leakage plays a role as firms with dense overlapping director networks experience faster propagation of technologies to competitors. Our findings suggest a coordination problem where industry participants cannot stop rivals from earning small gains from leakage despite much larger industry-wide negative externalities.